Pacari Brand Engagement and its Emotional Connection in Ethical Consumption - Córdova Duran, Edmundo Guillermo; Cornejo Mayorga, Ana del Rocío; Samaniego Arias, Mayra Alexandra; Cruz Oña, Ariel Omar; Alejandro Salazar , Giovanni David; Pazmiño Peñafiel, Erick Stalin (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The paper analyzes the factors that brand engagement produces in the growth of a brand, studying the values of creating emotional bonds to retain customers and develop consumer cultures. The PACARI brand is taken as a reference, which has international recognition, managing to position Ecuador as the country where the best chocolate in the world originates. The objective is to analyze the impact of PACARI and its connection in ethical consumption, where the brand has generated impact from the word of mouth marketing that it creates from influencers, and the commitment with its interest groups.